The joint involvement in adult onset Still's disease is characterised by a peculiar magnetic resonance imaging and a specific transcriptomic profile - Piero Ruscitti (Scientific Reports, 2021)
Abstract Adult onset Still's disease (AOSD) is a rare systemic autoinflammatory disease, characterised by fever, arthritis, and skin rash, and joint involvement is one of its clinical manifestations. The aims of this work were to assess joint involvement, to describe main patterns of involvement, and associated clinical characteristics. In this work, we aimed at assessing the joint involvement in AOSD by using MRI, to describe main patterns and associated clinical characteristics. In addition, we aimed at assessing the global transcriptomic profile of synovial tissues in AOSD to elucidate possible pathogenic pathways involved. We also evaluated the global transcriptomic profile of synovial tissues to elucidate possible pathogenic pathways involved in the disease. Thus, AOSD patients, who underwent to MRI exam on joints, were assessed to describe patterns of joint involvement and associated clinical characteristics. Some synovial tissues were collected for RNA-sequencing purposes. The most common MRI finding was the presence of synovitis on 60.5%, mainly in peripheral affected joints, with low to intermediate signal intensity on T1-weighted images and intermediate to high signal intensity on T2-fat-saturated weighted and STIR images. Bone oedema and MRI-bone erosions were reported on 34.9% and 25.6% MRI exams, respectively. Patients with MRI-bone erosions showed a higher prevalence of splenomegaly, a more frequent chronic disease course, lower levels of erythrocyte sedimentation rate, and ferritin. In AOSD synovial tissues, a hyper-expression of interleukin (IL)-1, IL-6, and TNF pathways was shown together with ferritin genes. In conclusion, in AOSD patients, the most common MRI-finding was the presence of synovitis, characterised by intermediate to high signal intensity on T2-fat-saturated weighted and STIR images. MRI-bone erosions and bone oedema were also observed. In AOSD synovial tissues, IL-1, IL-6, and TNF pathways together with ferritin genes resulted to be hyper-expressed.